Émile Mersch and theology of the russian diaspora - Pavel Khondzinskii (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия I. Богословие, философия)
In 1933 the Catholic scholar Emile Mersch published his work “The Mystical Body of Christ” (Le Corps mystique du Christ), in which the concept of the “mystical body” was traced from early Christian times to the beginning of the 20th century. Having paid tribute to Eastern fathers, Mersch believed that this concept reaches its final synthesis in the works of the “French school” authors in the 17th century, where the concept of personal mystical unity with Christ, dating back to the Rhine mystics, is combined with the idea of St. Cyril of Alexandria and St. Hilary of Pictavia of the “natural” unity of the Church in the Eucharist. Mersch considered this synthesis to be a complete expression of St. Augustine’s teachings of the Church as the “total Christ” (the whole Christ) - totus Christus. Some authors of the diaspora paid their attention to the Mersch’s monography. M. Lot-Borodina wrote a review to this work. Fr. Sergey Bulgakov used this work as a source of the references to blessed Augustine. But it was Fr. Georges Florovsky who treated this work most thoughtfully. In the description of his response to the Mersch’s work, we need to remember that initially Fr. Georges based on the position, which was formed in Russian theology by representatives of “new theology” at the beginning of the 20th century, first of all – the position of metropolitan Antony (Khrapovitsky). This position was characterized by the constitution of the unity of the Church on the moral rather than Eucharistic level. The moral level was regarded, because of the personalistic concept of the mutual transparency of persons, as a natural unity. The article traces the gradual evolution of Fr. Georges’s views from the above concept, through an attempt to combine the teaching of totus Christus with the teaching of metropolitan Anthony, to the unambiguously expressed Christological emphasis in ecclesiology. As a result, Florovsky's late ecclesiology reveals a certain closeness to the ecclesiology of the French school, and hence to Mersch’s general conceptual conclusions.